Determining demagnetisation risk for two PM wind power generators with different PM material and identical stators. Issue 7 (1st August 2016) - Sjökvist, Stefan; Eklund, Petter; Eriksson, Sandra
Abstract : Ways to utilise ferrite permanent magnets (PMs), in a better way has been in focus the last couple of years since the use of neodymium‐iron‐boron (NdFeB) PMs has been debated. While ferrite PMs offer a low‐cost alternative to rare‐earth PMs, it is a trade‐off for lower energy density. Depending on the type of PM and if the PMs are surface mounted or buried, the risk of demagnetisation during a fault condition can vary significantly between machines. In this study, the demagnetisation risk of two electrically similar generators with identical stators has been studied during several short‐circuit faults at different temperatures. The study is simulation‐based, and the results show that the generator with the ferrite rotor will suffer from a small but not significant amount of demagnetisation in the worst, three‐phase‐neutral, short‐circuit case at a temperature of 5°C, whereas the NdFeB PMs will suffer from partial demagnetisation if a fault occurs at 120°C. For operational temperatures between 20 and 60°C both generators will sustain a short‐circuit event.